2012
DOI: 10.1097/igc.0b013e31827277fa
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function of Patients With Endometrial Cancer Enrolled in the Gynecologic Oncology Group LAP2 Study

Abstract: Objectives To present responses to sexual function items contained within the quality of life (QOL) survey of the Gynecologic Oncology Group (GOG) LAP2 study, to investigate associations between sexual function and other factors such as relationship quality and body image), and to explore patterns of response in endometrial cancer patients. Methods Participants enrolled on the LAP2 QOL study arm completed a self-report QOL survey, which contained sexual function items, before surgery, and at 1, 3, 6-weeks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…Endometrial cancer survivor's sexual health can improve after the completion of treatment due to time alone (11, 31), potentially confounding the findings of longitudinal trials. Two prospective randomized trials for ECS demonstrated improvement in sexual health, with the first showing sexual function returning to baseline 6 months after surgery (11) and the second reporting that sexual activity and interest in patients receiving either external beam pelvic radiotherapy or vaginal brachytherapy increased for 6 month after starting treatment and plateaued thereafter (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endometrial cancer survivor's sexual health can improve after the completion of treatment due to time alone (11, 31), potentially confounding the findings of longitudinal trials. Two prospective randomized trials for ECS demonstrated improvement in sexual health, with the first showing sexual function returning to baseline 6 months after surgery (11) and the second reporting that sexual activity and interest in patients receiving either external beam pelvic radiotherapy or vaginal brachytherapy increased for 6 month after starting treatment and plateaued thereafter (31).…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective randomized trials for ECS demonstrated improvement in sexual health, with the first showing sexual function returning to baseline 6 months after surgery (11) and the second reporting that sexual activity and interest in patients receiving either external beam pelvic radiotherapy or vaginal brachytherapy increased for 6 month after starting treatment and plateaued thereafter (31). As our patients were recruited 6 months after completing therapy, the impact of the duration of time after diagnosis on sexual health should be minimal, which is supported by our participants’ similar baseline sexual health scores regardless of their time since diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that menopausal and lymphedema symptoms heavily affect QOL in EC patients. Sexual Activity scores improved until the 12-month evaluation (p = .048), and showed a return to baseline levels at the last assessment (p = .025) (Ferrandina et al, 2014 (Carter et al, 2012).…”
Section: Ferrandina Et Al Assessed Qol and Emotional Distress In A Smentioning
confidence: 95%
“…However, there was a problem with missing data and low comprehension of items related to sexuality. In our previous study (Stukan et al, 2014) (Carter et al, 2012). In the original study by Greimel et al (2011) 26% of the patients reported being sexually active.…”
Section: Discussionmentioning
confidence: 99%